Optical birefringence of liquid crystals for label-free optical biosensing diagnosis - Nguyen TT (Dove Medical Press, 2015)
Tan Tai Nguyen,1 Gyeo-Re Han,2 Chang-Hyun Jang,1,2 Heongkyu Ju1,3,4 1Department of Bionano Technology, 2Department of Nano-Chemistry, 3Department of Nano-Physics, Gachon University, Seongnam-City, 4Neuroscience Institute, Gil Hospital, Incheon, South Korea Purpose: We present a polarization-sensitive optical detection platform for label-free quantitative optical biosensing diagnosis using liquid crystals (LCs). This is capable of determining quantitatively the optical birefringence of optical cells containing LCs, whose orientation depends on the immobilized biomolecules.Patients and methods: This technique uses a polarization-dependent double-port detection without any polarizer at a single wavelength and removes the need of aligning optical cells of LCs in the azimuthal direction, with respect to the light path through the optical cell. Thus, this technique enables a stand-alone detection in a relatively compact format without an additional optical instrument, such as a retardation compensator, a Michael–Levy chart, and a spectrophotometer, in order to determine the optical birefringence quantitatively.Results: We demonstrate that bovine serum albumin immobilized on the gold surface of the cell hybrid interfaces that support both homeotropic and planar anchoring of LCs causes optical phase retardation change which can be determined quantitatively. We also provide estimation of the zenithal orientation of LCs near the gold surface of the hybrid interfaces, based on the phase retardation determined. The estimated limit of bovine serum albumin detection is approximately 2.1 µM.Conclusion: This optical technique with LCs can serve an optical platform for label-free quantitative diagnosis of proteins in a real time manner. Keywords: biological sensors, LC orientation, protein sensing, tag-free diagnosis